Pathophysiology and management of recreational drug-related acute coronary syndrome: ANMCO position statement. Issue 2 (February 2021) - Di Fusco, Stefania Angela; Rossini, Roberta; Flori, Marco; Pollarolo, Luigi; Ingianni, Nadia; Malvezzi Caracciolo D'Aquino, Marco; Galati, Giuseppe; Zilio, Filippo; Iorio, Annamaria; Scotto di Uccio, Fortunato; Lucà, Fabiana; Gulizia, Michele Massimo; et al.
Abstract : N/A: Recreational drug use may cause coronary artery disease through several mechanisms. An increasing number of young patients with drug-related acute coronary syndrome have been reported over recent years. The present position statement reports the most recent epidemiological data on acute coronary syndrome in the setting of drug abuse, describes the main pathophysiological mechanisms underlying coronary artery disease and acute events in these patients, and provides practical recommendations on management and an overview of prognosis.